The Current Situation of Using Internet Services in The Modern Organization of Training Sessions: Situasi Terkini Penggunaan Layanan Internet dalam Penyelenggaraan Sesi Pelatihan Modern - Abdusalyamovich, Djurayev Botir (Academia Open, 2024)
The modern use of Internet services in the organization of educational activities is a dynamically developing direction that radically changes traditional approaches to education. In the context of the rapid development of information technology, educational institutions are forced to adapt to the new reality by introducing innovative tools and platforms that provide access to educational resources, simplify the interaction between teachers and students, and also expand the possibilities of independently mastering the material. Highlights: Modern internet transforms traditional education approaches dynamically. Educational institutions adapt with innovative tools and platforms. Expands access, simplifies interaction, enhances independent learning opportunities. Keywords: Internet services, rapid development, information technology, between teachers and students